Fluid channeling along thrust zones: the Lagonegro case history, southern Apennines, Italy. Issue 2 (26th February 2013) - Gabellone, T.; Gasparrini, M.; Iannace, A.; Invernizzi, C.; Mazzoli, S.; D'Antonio, M.
Abstract A regional study on late burial, syntectonic dolomites and syntectonic calcite and quartz veins occurring in the hemipelagic Triassic–Jurassic succession of the Lagonegro Basin (southern Apennines) was carried out by integrating fieldwork with structural, fluid inclusion, and geochemical investigations on both surface and subsurface samples. The main goal was to characterize the different parent fluids, channeled along a major, out of sequence thrust zone. We also investigated calcite veins from the deeper tectonic mélange zone. The results point out that the fluids at peak burial conditions, during the first deformation stage, were characterized by temperatures of 120–140°C and salinities averaging 2 wt% NaCl eq. Fluids channeled along the late, out of sequence thrust zone and responsible for partial dolomitization of the succession had lower temperatures (Th = 95 ± 10°C) and salinities in the range of slightly modified to normal marine seawater (mean at 3.7 wt% NaCl eq). Similar low salinities are encountered in late dolomites from other fold‐and‐thrust belts of Italy. The most probable source for the fluids channeled along the investigated out of sequence thrust zone is represented by Miocene marine pore waters expelled from the tectonic mélange zone. A comparison of the Lagonegro dolomites with similar late stages carbonates formed in other fold‐and‐thrust belts suggests that fluid salinities appear to be controlled by the different lithologies of the fold‐and‐thrust belts décollement surfaces.